THE RELATIONSHIP BETWEEN THIKA TOWN AND BIRMINGHAM CITY AS CENTERS OF THE INDUSTRIAL REVOLUTION - Wangari, Virginia Murugi (IJRDO - Journal of Social Science and Humanities Research, 2023)
The current study explains the relationship between Thika Town and Birmingham City as centers of the industrial revolution. The main goal of this study is to understand the similarities in the development of the industries within Thika and Birmingham. The study also examines the similarities in the factors that led to industrialization in Thika and their effects on industrial growth. During data collection, the current study adopted an interpretive research paradigm where relevant data was collected using a literature review design. The data collection design involved identifying keywords and themes from existing literature on industrial development in Thika Town and Birmingham City. The data was later analyzed using thematic analysis, where information from the secondary data was grouped based on common themes. The study concludes with the research conclusions and recommendations.